DEVELOPMENT OF FUZZY LOGIC CONTROLLER FOR TRAINER KITBASED ON MICROCONTROLLER - Jamal, Zaidir; Rusydi, Maznur (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Informatics and Business Institute Darmajaya Bandar Lampung especially Bachelor of Computer System Program will apply FLC subjects on new curriculum in 2015. To increasing knowledge and motivation of students learning of Fuzzy Logic Controler/FLC is needed a trainer kit.          This study aimed to developed  FLC module for trainer kit. The membership function use a triangle.  The singleton fuzzification  use as fuzzifier.  FLC module is designed to have three subset with 9 rules. Fuzzy inference machine use max-min operator while defuzzification  use the Centre of Average. Fuzzy system implemented on ATmega 32 microcontroller then output converted to analogue using a DAC.         Testing is done by providing input voltage variations and measure the outputs and retrieve data from each of the fuzzy operations through data acquisition program. The test show the modules can work in accordance with the fuzzy operation, the output voltage of FLC module in accordance with changes in input voltage.  KEY WORDStrainer kit, fuzzy logic controller, microcontroller